Microstructure and Fatigue Properties of 6061 Aluminum Alloy Laser-MIG Hybrid Welding Joint - Cong Fan; Shanglei Yang; Minqi Zhu; Yishan Bai (Advances in Materials Science and Engineering)
Laser-MIG hybrid welding of 6061-T6 aluminum alloy was carried out with ER4043 welding wire, and the microstructure and fatigue properties of the joint were studied. The grain size of HAZ is larger than that of base metal (BM) due to the influence of welding heat cycle. Snowflake-like equiaxed grains were found in the upper, middle, and lower parts of the welded joint (WJ). Based on the fatigue test with 1 × 106 cycles, the ultimate fatigue strength of BM and WJ is 101.9 MPa and 54.4 MPa, respectively. There are many pores with different sizes in WJ. The number of pores in the upper and middle parts of WJ is obviously larger than that in the lower part due to the influence of the cooling rate of the weld pool and the escape rate of pores. The porosity type is mainly metallurgical pores with regular morphology, which is mainly due to the bubbles formed by the evaporation of Mg elements and H2O in the oxide film on the BM surface. The fatigue fracture analysis shows that the main cause of fatigue crack is the near-surface pores with 460 μm and 190 μm, respectively. The existence of pores near the surface is equivalent to the formation of a large-scale prefabricated crack, resulting in serious stress concentration. The morphology of the grains around the pores has a great influence on the initiation and propagation of the fatigue microcracks.